High-performance work practices and organisational performance in small firms: the role of guanxi. (3rd May 2016) - Yen, Yu-Fang; Wang, Hsing-Kuo; Kao, William
Abstract : This study adopted a contextual perspective to explore how interpersonal relationships in Chinese societies affected the relationship between high-performance work practices (HPWPs) and organisational performance. Interpersonal relationships, or guanxi, in the context of Chinese culture were discussed, and five manufacturing firms were examined using a qualitative case-study approach. The results revealed that HPWPs comprised cross-departmental training and education, performance-oriented evaluation, long-term client relationships, attractive salaries, teamwork, and morality. In addition, the results suggested that types of firm guanxi include external, inter-organisational, and intra-organisational guanxi. Intra-organisational guanxi directly affected HPWPs, whereas inter-organisational guanxi directly influenced organisational performance. External guanxi moderated the relationship between HPWPs and organisational performance. These findings contribute to academic research and practical applications.